2005
DOI: 10.1177/0164027504271438
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions and Early Retirement

Abstract: This article investigates the impact of working conditions on individual retirement for 270 occupations. It combines survey data for estimates of job strains, census data for occupations, and income and social insurance/security data, for the transition from work to retirement for 19,114 Norwegian employees between the ages of 60 and 67. Retirement was identified by a drop in work-related income and studied both jointly and separately for disability and nondisability retirement, including four types of disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(89 citation statements)
references
References 27 publications
8
79
1
1
Order By: Relevance
“…A low level of supportive leadership was the only predictor of work disability in the present study, an observation that is consistent with the findings of a study of the general working population in Finland (8,17). As in other general working population studies, we found that high job demand was not a significant predictor (6,12,15). By contrast, the finding that low decision control was not associated with work disability is contradictory to findings of previous general working population studies from Finland (31), Denmark (10), and Norway (11).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A low level of supportive leadership was the only predictor of work disability in the present study, an observation that is consistent with the findings of a study of the general working population in Finland (8,17). As in other general working population studies, we found that high job demand was not a significant predictor (6,12,15). By contrast, the finding that low decision control was not associated with work disability is contradictory to findings of previous general working population studies from Finland (31), Denmark (10), and Norway (11).…”
Section: Discussionsupporting
confidence: 93%
“…Other mechanical factors like prolonged standing (6), whole body vibration (7), and work in uncomfortable positions (8) have been discussed as possible risk factors, but the evidence still remains limited (9). Low job control at work (eg, little influence on the work situation and decision authority) appears to be the most consistent work-related psychosocial risk factor (10)(11)(12)(13)(14). Some studies have indicated that job strain (15,16), lack of social support (8,17), and job demands (14) may be important.…”
mentioning
confidence: 99%
“…It is likely that grandparents who became grandparents early also had an early transition to parenthood, particularly among the low-educated. Low education and early transition to parenthood have been linked to poor health and higher mortality as well as early retirement (Blekesaune and Solem 2005;Grundy and Kravdal 2008;Hank and Korbmacher 2013;Ross and Mirowsky 2010). Hence, low education and early parenthood may mediate early retirement among grandparents.…”
Section: Theoretical Considerations Empirical Evidence and Hypothesesmentioning
confidence: 99%
“…For instance, higher educated workers generally have higher wages and access to more stable jobs (Blöndal & Scarpetta, 1998) and less physically strenuous jobs. Research indicates that higher educated workers usually retire at a later age than lower educated workers, which is partly because they are less at risk of developing health problems such as musculoskeletal diseases (Blekesaune & Solem, 2005).…”
Section: Differences Across Countries and Specific Groups Of Peoplementioning
confidence: 99%
“…The vast literature on (early) retirement has already defined several influential factors, economic ones such as labour demand shifts associated with the knowledge economy and increased international competition, institutional ones associated with the extension and generosity of the social protection system, and social ones associated with individual and household demographics, health and working conditions, and policy context (Duval, 2003;Blekesaune & Solem, 2005;Davey, 2008), but so far little attention has been paid to the influence of personal preferences and social norms in society in relations to labour law and social security. This chapter acknowledges the importance of economic incentives to retire and therefore examines the effect of the generosity of old-age pensions (measured through pension replacement rates) on the retirement decision, but also focuses on the influence of social norms regarding the importance of work and leisure time.…”
Section: Introductionmentioning
confidence: 99%